Optimization Of The Ferrite Core Volume In A Single-phase Grid-connected Pv System With Active And Reactive Power Control - de Souza, Kleber C. A.; dos Santos, Walbermark M.; Martins, Denizar C. (Eletrônica de Potência, 2013)
This paper presents a method to minimize the losses and the magnetic cores volume in a single-phase active power filter based in a two stages grid-connected PV system. The proposed circuit injects PV generated power into the utility, and always acts as an active power filter to compensate load harmonics and reactive power such that the input power factor is very high independently of the solar radiation and the type of the load connected. In sunny days, the system processes all the reactive and active load power and the excessive power from the PV module can be fed to the utility. On the other hand, on cloudy days for instance, if the PV power is not enough, the system processes all the reactive load power and the shortage of active load power is supplemented by the utility. Besides, just using one current sensor, the control strategy is simple and of suitable for practical implementation.